DEVELOPING YOUTH RESILIENCE IN CONDITIONS OF SOCIAL INSTABILITY AND WAR - Vira Syniakova; Yuliia Bokhonkova; Mykyta Minin (Alfred Nobel University Journal of Pedagogy and Psychology, 2025)
In the context of ongoing social instability and armed conflict in Ukraine, the issue of youth resilience has become increasingly relevant. Adolescence is a critical stage of psychological development, marked by the formation of identity, social roles, and future aspirations, making this age group particularly vulnera- ble to the impact of traumatic experiences. The full-scale war in Ukraine has intensified psychological stress among youth, resulting in heightened levels of anxiety, emotional instability, and symptoms of post-traumatic stress disorder (PTSD). In such circumstances, resilience becomes a key psychological resource that enables individuals to adapt to stress, recover after adversity, and maintain emotional well-being. The aim of this study is to determine the psychological features of resilience formation among youth in conditions of social instability and military conflict, and to outline effective strategies for its development and support. The research is based on a systemic approach, which views resilience as a multidimensional phenom- enon that integrates cognitive, emotional, motivational, behavioural, and social components. The theoreti- cal analysis incorporates various conceptual frameworks, including personal, resource, processual, and sys- temic approaches. The paper distinguishes between the notions of “resilience” as a process and “resiliency” as an individual capacity or trait, drawing on international and domestic psychological theories. Methodologically, the study involved the implementation and evaluation of an 8-week resilience de- velopment program for Ukrainian youth, consisting of interactive modules on self-awareness, emotional regulation, stress coping, communication, critical thinking, motivation, and life planning. Methods used in- cluded cognitive-behavioural techniques, mindfulness practices, logotherapy, art therapy, and group train- ing sessions. The effectiveness of the program was assessed through pre- and post-program questionnaires and qualitative feedback from participants. In addition, an online support platform (Telegram channel) was created to enhance engagement and provide supplementary materials such as motivational content and guided practices. The results demonstrate a significant improvement in participants’ emotional stability, motivation, coping strategies, and critical thinking abilities. Particularly effective were the modules focused on emo- tional literacy, adaptive coping mechanisms, and community-based support. The program participants re- ported increased self-efficacy, improved ability to manage stress, and greater involvement in social interac- tions. The findings are consistent with national and international studies emphasizing the critical role of so- cial support, adaptive coping, emotional regulation, and positive thinking in the development of resilience. The conclusion affirms that resilience is a dynamic and developable capacity, especially vital for youth experiencing war-related trauma. Targeted psychological, educational, and social interventions can signif- icantly contribute to building this capacity. The study highlights the need for systematic psychological sup- port programs aimed at youth, particularly in crisis contexts. Future research should focus on the long-term effects of resilience development programs and explore scalable models for broader implementation across educational and social institutions. In summary, the formation of resilience in youth is an essential direction for modern psychological as- sistance, ensuring mental health preservation, adaptive success, and personal growth in the face of con- temporary challenges. Under conditions of military conflict, developing resilience becomes not only a pro- tective factor but also a foundation for post-traumatic growth and national recovery.